Control de inventario para agilizar la gestión de bodega en tcp don neptalí en el cantón El Guabo año 2023. - Cojitambo Arcentales, Ginger Anabel (Machala : Universidad Técnica de Machala, 2024)
In every organization, the correct management and control of inventories is important, allowing adequate business performance. The NIC2 inventory account is a relevant asset, because all SMEs depend on it to generate profits reflected in the Financial Statement. Efficient inventory management not only guarantees an adequate balance between supply and demand, but also It has a direct impact on corporate profitability. An excess of stock can lead to additional storage costs and depreciation, while a shortage can result in lost sales and customer discontent. The present investigation is carried out in the Palmar Don Neptalí Community Store, located in the Guabo canton, dedicated to the sale of essential products, especially the marketing of Palmar rice to the Guabeña community for approximately four years, its main problem It is the inadequate inventory control and the lack of regulations that allow efficient optimization of merchandise, causing losses for business interests and affecting employees, because they assume the sanctions imposed by management. The objective of the research is to determine the causes of inefficient inventory control in the warehouse management of the TCP Don Neptalí in the El Guabo Canton during the period 2023. The methodology used in the study is transversal in nature, taking as reference the documentary information of the financial instruments of the fiscal period 2022-2023, using a descriptive quantitative approach, using the non-participatory observation method, technical verification sheets, interviews with depth and analysis of secondary data recovered in indexed scientific bases such as Scopus, Dialnet, Redalyc, Scielo. The main findings of the investigation determine that the company is not governed by management policies for the control of merchandise in the warehouses, the lack of continuous training techniques for personnel has caused errors such as incorrect billing, low turnover of items, inconsistency in the storage and registration of stock, which contrasts the information on hangers of certain products with the Kardex of the accounting program. The investigative findings will allow the establishment of an implementation process supported by key regulations and strategies for adequate merchandise management, avoiding causing losses and deterioration of stock, generating the inventory in accordance with the accounting instruments. Inventory management accompanied by computer programs minimizes errors, guarantees durability, rotation of goods, timely monitoring of entries, exits, expiration, and stocking of stock available for sale. In addition, staff training techniques will generate a commitment to manage and care for assets and guide them towards the company's objectives, achieving sales goals and building customer loyalty. This investigative work will serve to understand the importance of inventory control, its management and accounting policies that help avoid situations that harm the stability and profitability of the company in its Financial Statements, avoid sanctions to personnel, help in making purchasing decisions. of new products analyzing costs and their rotation, safeguarding merchandise for sale, managing to satisfy customer demand.
En toda organización es importante el correcto manejo y control de los inventarios, permitiendo un adecuado rendimiento empresarial. La cuenta de inventario NIC2, es un activo de relevancia, porque todas las pymes dependen de ella para generar ganancias reflejadas en el Estado Financiero, una administración eficiente de los inventarios no solo garantiza un equilibrio adecuado entre la oferta y la demanda, sino que también tiene un impacto directo en la rentabilidad corporativa. Un exceso de existencias puede generar gastos adicionales por almacenamiento y depreciación, mientras que una escasez puede resultar en pérdida de ventas y descontento por parte de los clientes. La presente investigación se desarrolla en la Tienda Comunitaria Palmar Don Neptalí, ubicada en el cantón el Guabo, dedicada a la venta de productos de primera necesidad, especialmente a la comercialización de arroz Palmar a la comunidad guabeña desde hace cuatro años aproximadamente, su principal problemática es el inadecuado control de inventario y la carencia de normativas que permitan una eficiente optimización de la mercadería, provocando pérdidas para los intereses empresariales e incidiendo en los colaboradores, debido a que asumen las sanciones impuestas por parte de la gerencia. El objetivo de la investigación es Determinar las causas del ineficiente control de inventario en la gestión de bodega de la TCP Don Neptalí en el Cantón El Guabo periodo 2023. La metodología empleada en el estudio es de carácter transversal tomando como referencia la información documental de los instrumentos financieros del periodo fiscal 2022-2023, utilizando un enfoque cuantitativo de tipo descriptivo, empleando el método de observación no participativa, fichas de verificación técnica, entrevista a profundidad y análisis de datos secundarios recuperados en bases científicas indexada como Scopus, Dialnet, Redalyc, Scielo. Los principales hallazgos de la investigación determinan que la empresa no se rige por políticas gerenciales para el control de mercadería en las bodegas, la carencia de técnicas de capacitación continua al personal ha ocasionado errores como la incorrecta facturación, baja rotación de artículos, inconsistencia en el almacenamiento y registro del stock, lo que se contrasta a la información en perchas de ciertos productos con el Kardex del programa contable. Los hallazgos investigativos permitirán instaurar un proceso de implementación sustentado en las normativas y estrategias clave para una adecuada gestión de mercancías, evitando ocasionar perdidas, deterioro del stock, generando que el inventario sea acorde con los instrumentos contables. La gestión del inventario acompañada de programas informáticos minimiza errores, garantiza la durabilidad, rotación de los bienes, seguimiento oportuno de entradas, salidas, vencimiento, perchado de la existencia disponible para la venta. Además, las técnicas de capacitación al personal van a generar un compromiso de manejo y cuidado de los activos y orientan hacia los objetivos de la empresa, en alcanzar metas de ventas y fidelizar clientes. Este trabajo investigativo servirá para conocer la importancia del control de inventarios, su gestión y políticas contables que ayudan a evitar situaciones que perjudiquen la estabilidad y rentabilidad de la empresa en sus Estados Financieros, evitar sanciones al personal, ayudar a la toma decisiones en la compra de productos nuevos analizando los costos y su rotación, salvaguardando la mercadería para la venta, logrando satisfacer la demanda de los clientes.
Keywords: CONTROL INTERNO; GESTIÓN EMPRESARIAL; NIC 2; ESTADOS FINANCIEROS